Effect of Cinnamaldehyde on C. albicans cell wall and (1,3)- β - D-glucans in vivo - Jie-Hua Deng; Xiao-Guang Zhang; Gang-Sheng Wang; Jing-Na Luo; Jia Wang; Xiao-Ming Qi; Yan-Ling Li (BMC, 2022)
Abstract Background The incidence rate of invasive candidiasis is high, its treatment is difficult, and the prognosis is poor. In this study, an immunosuppressive mouse model of invasive Candida albicans (C. albicans) infection was constructed to observe the effects of cinnamaldehyde (CA) on the C. albicans cell wall structure and cell wall (1,3)-β-D-glucan contents. This study provides a theoretical basis for CA treatment to target invasive C. albicans infection. Methods Immunosuppressed mice with invasive C. albicans infection were given an oral dosage of CA (240 mg.kg− 1.d− 1) for 14 days. Then, mouse lung tissue samples were collected for detection of the levels of (1,3)-β-D-glucan and transmission electron microscopy observations, using fluconazole as a positive control and 2% Tween 80 saline as a negative control. Results The immunosuppressive mouse model of invasive C. albicans infection was successfully established. The levels of (1,3)-β-D-glucan in the CA treatment group, fluconazole positive control group, invasive C. albicans infection immunosuppressive mouse model group, and 2% Tween 80 normal saline control group were 86.55 ± 126.73 pg/ml, 1985.13 ± 203.56 pg/ml, 5930.57 ± 398.67 pg/ml and 83.36 ± 26.35 pg/ml, respectively. Statistically, the CA treatment group, fluconazole positive control group and invasive C. albicans infection immunosuppressive mouse model group were compared with each other (P < 0.01) and compared with the 2% Tween 80 saline group (P < 0.01), showing that the differences were very significant. Comparison of the CA treatment group with the fluconazole positive control group (P < 0.05) displayed a difference as well. Electron microscopy showed that CA destroyed the cell wall of C. albicans, where the outer layer of the cell wall fell off and became thinner and the nuclei and organelles dissolved, but the cell membrane remained clear and intact. Conclusion CA destroys the cell wall structure of C. albicans by interfering with the synthesis of (1,3)-β-D-glucan to kill C. albicans. However, CA does not affect the cell membrane. This study provides a theoretical basis for CA treatment to target invasive C. albicans infection.